The effect of digital literacy on women’s intentions to report gender-based violence among womenspirasi summit participants - Afifah, Mujahidah; Ruhimat, Ruhimat; Setiawan, Koesworo (Priviet Social Sciences Journal, 2026)
This study examines the effect of digital literacy on women’s intentions to report gender-based violence among participants of the Womenspirasi Summit. Employing a quantitative explanatory design, data were collected through an online survey distributed to 212 female participants selected using purposive sampling. Digital literacy was measured using a multidimensional framework adapted from UNESCO, while reporting intention was analyzed through the Theory of Plannssed Behavior, encompassing attitudes toward the behavior, subjective norms, and perceived behavioral control. Data were analyzed using descriptive statistics and simple linear regression with IBM SPSS 25. The findings indicate that participants exhibit a very high level of digital literacy (mean = 4.34) and a very strong intention to report gender-based violence (mean = 4.54). Regression analysis demonstrates that digital literacy has a positive and statistically significant effect on reporting intention (β = 0.498; p < 0.001), accounting for 61.2% of the variance in reporting intention. These results suggest that digital literacy enhances women’s perceived control over the reporting process, fosters positive attitudes toward reporting, and strengthens supportive social norms within digital and community-based environments. The study concludes that digital literacy is a key determinant in increasing women’s intentions to report gender-based violence, highlighting the importance of integrating digital literacy development into gender-based violence prevention and response strategies to address underreporting and promote access to justice.